Unravelling decision making about the future developments of Amsterdam Airport Schiphol - Martijn Van Boxtel; Menno Huys (European Regional Science Association (ERSA), 2005)
The time that airports were merely infrastructural works for supporting air transportation is no more. Over the years, especially the major airports have developed from airfields into multi-modal transportation nodes and cities of their own. Amsterdam Airport Schiphol is a perfect example of this. The airport has developed into an attractive pool for urban and economic development, known as an AirportCity. Airports like Amsterdam Airport Schiphol, took up their newfound position in the emerging network society and implemented new business strategies to cope with the increasing volatility of future transport volumes. The search for additional finances has lead to further commercialization of the airport and gave rise to Airport-city like concepts. However, this evolving form of airports did not find its way into Dutch national planning policy. An analysis of Dutch national spatial strategies shows an increased interest for Amsterdam Airport Schiphol as being of major importance for the national economy, but the emphasis is still mainly on the airport as an important piece of physical infrastructure. With fierce competition of cities like Barcelona and Dublin in mind, the Amsterdam region needs a strong, widely supported, development strategy to maintain and strengthen its concurrence position. A strategy that acknowledges the new airport day-to-day realities and that goes beyond the narrow definition of the airport as merely infrastructural. Such a widely accepted strategy does not exist at this moment, which causes serious problems if policies are willing to strengthen the role of Schiphol for the national economy in the future. This paper explores the newfound position of airports in the network society. It links this position to an analysis of the processes of policy making to identify reasons why there is currently no strong development strategy for Amsterdam Airport Schiphol (region). A comparison is made between the policy development process in the late 80's and early 90's, which did result in a widely accepted development policy for the airport, and the policy development process that currently takes place. Interviews with primary stakeholders and analyses of policy documents shed light on the success factors that made the reach of an agreement possible in the early 90's as well as the reasons for not being able to reach such agreement today.
Keywords: 330